Student’s acceptance of the Nearpod application: an investigation in elementary school - Rizky Amelia; Zamzani Zamzani; Ali Mustadi; Ahmad Suriansyah; Aslamiah Aslamiah (Institute of Advanced Engineering and Science, 2024)
The use of technology can increase teacher innovation in carrying out mass learning. Innovations that can standardize in terms of media use or digital supporting devices that reduce the learning barrier and help students succeed. One of the components of multimedia-based learning media is the Nearpod application. This research aims to ascertain the purpose and behavior of primary school pupils utilizing the Nearpod application via an extension of the unified theory of acceptance and use of technology 2 (UTAUT 2) model. The researchers employed a quantitative research method by distributing questionnaires to 217 students at Public Elementary School (SDN) 004 Tanjung Redeb, Berau Regency, East Kalimantan, Indonesia. Data from this study were analyzed using partial least square structural equation modeling (PLS-SEM). The findings revealed that behavioral intention (BI) is significantly positively influenced by hedonic motivation (HM), habit (H), and habitual behavior (HB). In addition, habit (H) also has a significant positive effect on use behavior (UB). It can conclude this study can explain that the adoption of technology in the elementary school environment has different causal factors.